2022
DOI: 10.1039/d2nj00256f
|View full text |Cite
|
Sign up to set email alerts
|

The use of electrostatic potential at nuclei in the analysis of halogen bonding

Abstract: The molecular electrostatic potential (MESP) at the nuclei of a large heterogeneous set of halogen bonded complexes calculated at M06-2X/aug-cc-pVTZ level of theory, is studied. The halogen bond formation leads...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…The ΔΔ V n showed a good linear correlation with the noncovalent interaction energy, E int (Figure ). A recent study confirmed that the strength of even very weakly halogen-bonded systems can be explained in terms of the subtle fluctuation that occurs in the MESP at closely interacting atoms . This study also showed that, in contrast to MESP surface analysis, MESP topological analysis of halogen bonding is more reliable and accurate.…”
Section: Hydrogen Bonding and Other Noncovalent Interactionssupporting
confidence: 53%
See 2 more Smart Citations
“…The ΔΔ V n showed a good linear correlation with the noncovalent interaction energy, E int (Figure ). A recent study confirmed that the strength of even very weakly halogen-bonded systems can be explained in terms of the subtle fluctuation that occurs in the MESP at closely interacting atoms . This study also showed that, in contrast to MESP surface analysis, MESP topological analysis of halogen bonding is more reliable and accurate.…”
Section: Hydrogen Bonding and Other Noncovalent Interactionssupporting
confidence: 53%
“…A recent study confirmed that the strength of even very weakly halogenbonded systems can be explained in terms of the subtle fluctuation that occurs in the MESP at closely interacting atoms. 49 This study also showed that, in contrast to MESP surface analysis, MESP topological analysis of halogen bonding is more reliable and accurate. The ΔΔV n versus E int correlation unifies hydrogen-bonded and other noncovalently bonded complexes to a single category, the eDA complex.…”
Section: Hydrogen Bonding and Other Noncovalent Interactionsmentioning
confidence: 70%
See 1 more Smart Citation
“…The positions of V min and V max are marked in Figure . During the complex formation between X and H 2 O, there is a change in corresponding MESP maxima and minima, and the magnitude of these MESP changes are designated as Δ V max and Δ V min , respectively. , Thus, Δ V max = V max_iso – V max_com , where V max_iso and V max_com are V max located on a particular site of isolated species and its interacted complex, respectively. Similarly, we can define Δ V min , and its magnitude is a rough estimate of the change in the electron density during complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…For nitroaromatic explosives, values of positive potential at the critical points (CPs) located above the aromatic rings could be used to assess trends in sensitivity toward detonation. Critical points represent the most electron-rich (V min ) or electron-depleted (V max ) sites of the molecular electrostatic potential [13]. It is important to point out that molecular electrostatic potential is the physical characteristic of a molecule which could be both experimentally determined and calculated by ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%